Mobilising Common Biocultural Heritage for the Socioeconomic Inclusion of Small Farmers: Panarchy of Two Case Studies on Quinoa in Chile and Bolivia - Saez-Tonacca, L (Springer Science and Business Media B.V., 2020)
Valorising the biocultural heritage of common goods could enable peasant farmers to achieve socially and economically inclusive sustainability. Increasingly appreciated by consumers, peasant heritage products offer small farmers promising opportunities for economic, social and territorial development. Identifying the obstacles and levers of this complex, multi-scale and multi-stakeholder objective requires an integrative framework. We applied the panarchy conceptual framework to two cases of participatory research with small quinoa producers: a local fair in Chile and quinoa export production in Bolivia. In both cases, the “commoning” process was crucial both to bring stakeholders together inside their communities and to gain outside recognition for their production and thus achieve social and economic inclusion. Despite the differences in scale, the local fair and the export market shared a similar marketing strategy based on short value chains promoting quality products with high identity value. In these dynamics of biocultural heritage valorisation, the panarchical approach revealed the central place as well as the vulnerability of the community territory. As a place of both anchoring and opening, the community territory is the privileged space where autonomous and consensual control over the governance of common biocultural resources can be exercised. © 2019, Springer Nature B.V.